An Investigation of the Level of Heavy Metals Contamination of Goat Meat Roasted with Scrap Tyres in Wukari, Nigeria - Joseph, Ikwebe; David, Bando Christopher; Agyo, David Ata; Tadawus, Rejoice Habila (Darul Yasin Al Sys, 2024)
The present study was undertaken to investigate the potential for heavy metals (Fe, Cr, Cd, Pb, and Cu) contamination of goat meat roasted with scrap tyres in Wukari using atomic absorption spectrophotometer (AAS). Goat meat samples were obtained from two slaughter points (new market and Mammara). The results revealed the mean concentrations of Fe, Cr, and Cu in the unroasted goat meat samples (UMN and UMM) in both new market and Mammara slaughtering points as 1.7600 ± 1.4000, 0.0012 ±0.0000, 0.8700, 3.2500 ± 0.0000, 0.0025 ± 0.0000, and 0.7850 ± 0.0071 mg/kg respectively. Cd and Pb were not detected in any of the samples. The mean concentrations of Fe, Cr, Cd, and Cu in the goat meat roasted with scrap tyres (RMN1 and RMM1) in both slaughtering houses (new market and Mammara) were 4.1300 ± 0.0141, 0.0025 ± 0.0001, 0.0011 ± 0s.0000, 1.1250 ± 0.0071, 5.1500 ± 0.0000, 0.0035 ± 0.0001, 0.0012 ± 0.0000, and 1.0500 ± 0.0000 mg/kg respectively. Pb was not detected in all the samples. Also, the mean concentrations of Fe, Cr, and Cu in the goat meat roasted with firewood (RMN2 and RMM2) in slaughtering houses (new market and Mammara) were 3.7750 ± 0.0000 mg/kg, 0.0013 ± 0.0000, 0.9850 ± 0.0000, 4.9150 ± 0.0071, 0.0026 ± 0.0000, and 0.8650 ± 0.021 mg/kg respectively. Cd was detected in the samples obtained from Mammara (0.0012 ± 0.0000) but was not detected in the samples collected from new market. Pb was not detected in any of the samples obtained from both slaughtering houses. The mean concentrations of Fe and Cu in (UMN, UMM), (RMN1, RMM1), and (RMN2, RMM2) in both slaughtering points were above the maximum permissible level set by (FAO) and (WHO).The result of this present study show that the practice of roasting goat meat with scrap tyres is dangerous because the meat could accumulate high and unacceptable levels of heavy metals that could pose a threat to human lives, and hence, should be outlawed.